Neuron-specific responses to acetylcholine within the spinal dorsal horn circuits of rodent and primate. (15th October 2021) - Sykes, Matthew J.; Kekesi, Orsolya S.; Wong, Yan T.; Zhao, Fei-Yue; Spanswick, David; Imlach, Wendy L.
Abstract: Excitatory and inhibitory neurotransmission within the spinal dorsal horn is tightly controlled to regulate transmission of nociceptive signals to the brain. One aspect of this control is modulation of neuronal activity through cholinergic signaling. Nociceptive neurons in the dorsal horn express both nicotinic and muscarinic cholinergic receptors and activation of these receptors reduces pain in humans, while inhibition leads to nociceptive hypersensitivity. At a cellular level, acetylcholine (ACh) has diverse effects on excitability which is dependent on the receptor and neuronal subtypes involved. In the present study we sought to characterize the electrophysiological responses of specific subsets of lamina II interneurons from rat and marmoset spinal cord. Neurons were grouped by morphology and by action potential firing properties. Whole-cell voltage-clamp recordings from lamina II dorsal horn neurons of adult rats showed that bath applied acetylcholine increased, decreased or had no effect on spontaneous synaptic current activity in a cell-type specific manner. ACh modulated inhibitory synaptic activity in 80% of neurons, whereas excitatory synaptic activity was affected in less than 50% of neurons. In whole-cell current clamp recordings, brief somatic application of ACh induced cell-type specific responses in 79% of rat lamina II neurons, which included: depolarization and action potential firing, subthreshold membrane depolarization, biphasic responses characterized by transient depolarization followed by hyperpolarization and membrane hyperpolarization alone. Similar responses were seen in marmoset lamina II neurons and the properties of each neuron group were consistent across species. ACh-induced hyperpolarization was blocked by the muscarinic antagonist atropine and all forms of acetylcholine-induced depolarization were blocked by the nicotinic antagonist mecamylamine. The cholinergic system plays an important role in regulating nociception and this study contributes to our understanding of how circuit activity is controlled by ACh at a cellular level in primate and rodent spinal cord. Graphical abstract: Image 1 Highlights: ACh increases inhibitory signaling to excitatory radial and vertical neurons, reducing nociceptive output. ACh reduces inhibitory signalling to inhibitory islet neurons, reducing nociceptive output. No species-specific differences in ACh signalling were found in the rodent and primate dorsal horn.